Vincristine-induced peripheral neuropathy in children with malignancy and the effect of missed doses on treatment success - EKER, NURŞAH (My University, 2023)
Introduction: Recognizing the symptoms of vincristine-induced peripheral neuropathy (VIPN) earlier is crucial to preventing the persistent neurological sequelae. The treatment of neuropathy is to discontinue the drug, and the effect of a missed dose of vincristine on treatment success is unclear. This study aims to evaluate VIPN in children with malignancy and the effect of skipping vincristine doses on the treatment success of patients at a single center, retrospectively. Methods: Medical records of the children with cancer who received vincristine in our institution between 2013 and 2020 were analyzed retrospectively. Results: Vincristine neuropathy was found in 42 (7%) of 598 pediatric patients who received at least one dose of vincristine during the study period. Neuropathy developed at a statistically significantly lower cumulative dose in patients younger than seven years of age (p=0.04). The mean neuropathy duration of the cases was 8.5 months, and the findings of 40 (95.2%) cases improved. The mean cumulative dose was higher in patients with diffuse nerve involvement. The missed dose of vincristine was lower in the cases in complete remission compared to the other cases and higher doses of vincristine were missed in the stable disease group than in the remission group (p=0.03). Conclusion: VIPN can be encountered in less cumulative doses, mainly in the younger age group. Missed doses of vincristine may affect treatment success, and more comprehensive studies are needed to show this effect more clearly.
Keywords: chemotherapy; children; cancer; peripheral neuropathy; vincristine